Digital Literacy for State Apparatus in Supporting Makassar City as a Metaverse City: Case Study at the Makassar City Communication and Informatics Office - Ilham, A. Fifah Ilyana; Uluputty, Irfan; Faqih, Naufal (Indonesian Journal of Librarianship, 2023)
Abstract Problems: This research addresses the readiness of civil servants (ASN) in welcoming the government's initiative to make Makassar City as a Metaverse City. Objective: The objective of this study is to illustrate the competencies of ASN in contributing to digital literacy improvement in Makassar City. Method: The research methodology uses a qualitative approach with a descriptive method that explores ASN literacy information in Makassar City using the DQ Institute indicators, namely: Skill, Knowledge, and Attitude. Descriptive reinforcement is achieved through data triangulation. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. Findings: The findings in the Knowledge dimension indicate that ASN has fulfilled the indicators of information needs and data validity, demonstrating a cautious approach to manage information to avoid critical errors. In the Skill dimension, it was found that employees are proficient in operating digital system of ICT. In the Attitude dimension, the research discovered a high level of competency in producing accurate, tested information sources and effectively managing that information to achieve specific goals. Conclusion: This study concludes that the competence of ASN in building digital literacy within the Communication and Informatics Office of Makassar City has progressed effectively. Overall, ASN can adapt to use digital systems in public services and actively participate in digitally-based service innovations. Keywords: ASN. Metaverse City,.Digital Literacy, Artificial Intelligence.